Chocolate ingestion in dogs: 156 events (2015–2019). (31st March 2021) - Weingart, C.; Hartmann, A.; Kohn, B.
Abstract : Objectives: To describe the clinical features and outcome of dogs after chocolate ingestion. Material and Methods: Retrospective evaluation of clinical signs, clinical pathological findings, therapy and outcome of 156 dogs after chocolate ingestion. The concentration of methylxanthines (theobromine, caffeine) was calculated based on the type of chocolate and the amount ingested. Results: One hundred and twelve dogs had no clinical signs. Forty‐four dogs had clinical signs of chocolate intoxication. Twenty‐eight of these 44 dogs ingested dark and bitter chocolate. Reasons for presentation were agitation (33), tremor (22), vomiting (21), panting (11), polyuria/polydipsia (seven) and diarrhea (two). Common clinical findings were sinus tachycardia (28), tachypnea/panting (14), hyperthermia (10) and dehydration (seven). Clinical pathological findings in 34 of 44 dogs consisted of hyperlactataemia (23), hypokalaemia (16), mild hyperglycaemia (16) and mild alanine aminotransferase (ALT) and aspartate aminotransferase (AST) elevation (14). After decontamination (apomorphine, activated carbon) and symptomatic treatment (fluid therapy, esmolol, forced diuresis, sedatives), 43 of the 44 dogs survived. Clinical Significance: In dogs with potential chocolate intoxication, the type and amount of chocolate and the time of ingestion are important factors. Cardiovascular, neurological and gastrointestinal signs are the most common clinical signs. In this case series, the prognosis after decontamination and symptomatic therapy was good, with a mortality rate of less than 3%.